2016
DOI: 10.1021/acsami.6b11393
|View full text |Cite
|
Sign up to set email alerts
|

Carbon-Based CsPbBr3 Perovskite Solar Cells: All-Ambient Processes and High Thermal Stability

Abstract: The device instability has been an important issue for hybrid organic-inorganic halide perovskite solar cells (PSCs). This work intends to address this issue by exploiting inorganic perovskite (CsPbBr) as light absorber, accompanied by replacing organic hole transport materials (HTM) and the metal electrode with a carbon electrode. All the fabrication processes (including those for CsPbBr and the carbon electrode) in the PSCs are conducted in ambient atmosphere. Through a systematical optimization on the fabri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
182
0
4

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 272 publications
(196 citation statements)
references
References 49 publications
10
182
0
4
Order By: Relevance
“…[45] Luther's group found that the device based on the as-obtained α-CsPbI 3 QDs film exhibited operational stability and tolerance to higher relative humidity levels (Figure 12). [149,150] Although the PCEs of these novel solar cells are not quite as high (the reported values are 5.0% and 6.7% in the case of CsPbBr 3 solution-processed film as light absorber layer, respectively, by the aforementioned two groups), they found that the entire fabrication process of cell architecture can be conducted in ambient environment without humidity control (e.g., a glovebox). [45] All-inorganic perovskite solar cells using carbon paste as both hole-transporter and cathode have independently reported by Chen et al and Jin's group at almost the same time.…”
Section: Photovoltaic Devicesmentioning
confidence: 98%
See 3 more Smart Citations
“…[45] Luther's group found that the device based on the as-obtained α-CsPbI 3 QDs film exhibited operational stability and tolerance to higher relative humidity levels (Figure 12). [149,150] Although the PCEs of these novel solar cells are not quite as high (the reported values are 5.0% and 6.7% in the case of CsPbBr 3 solution-processed film as light absorber layer, respectively, by the aforementioned two groups), they found that the entire fabrication process of cell architecture can be conducted in ambient environment without humidity control (e.g., a glovebox). [45] All-inorganic perovskite solar cells using carbon paste as both hole-transporter and cathode have independently reported by Chen et al and Jin's group at almost the same time.…”
Section: Photovoltaic Devicesmentioning
confidence: 98%
“…[45] All-inorganic perovskite solar cells using carbon paste as both hole-transporter and cathode have independently reported by Chen et al and Jin's group at almost the same time. [149,150] Hence, these exciting results make practical application of all-inorganic perovskite photovoltaic devices a real possibility after further improving the overall performances. In particular, they also found that as-fabricated devices without encapsulation exhibited remarkable stability even under harsh conditions such as high-humidity conditions (e.g., 90−95% relative humidity) and extreme temperatures (e.g., 100 or −22 °C) (see Figure 12).…”
Section: Photovoltaic Devicesmentioning
confidence: 99%
See 2 more Smart Citations
“…[44] In a cross-point array, this should be solved. Cesium-hybridized solar cells and all-inorganic CsPbBr 3 -based resistive switching memory devices fabricated using solution process have been reported, [50,51] and recently, a vacuum codeposition method [52] was introduced to fabricate efficient Cs-based inorganic perovskite solar cells. [46] Moreover, various selector materials have been developed, [47][48][49] so in the future selector devices may be integrated with the perovskite memory devices.…”
Section: Metal Halide Perovskitesmentioning
confidence: 99%